Respuestas

  • Usuario de Brainly
2013-11-12T15:31:01+01:00
3x-4y=-6
2x+4y=16

2 (3x-4y= - 6)-------------6x-8y=-12
-3 (2x+4y=16)----------  -6x-12y=-48
                                 ------------------
                                    -20y= -60
                                         y=-60/-20
                                         y=3
2x+4(3)=16
2x=16 - 12
x=2
R= x=2    y=3

3x+2y= 7
4x-3y= -2

3(3x+2y=7)-------------9x+6y=21
2(4x-3y=-2)-------------8x-6y=-4
                             -----------------
                             17x    =17
                                  x=  1
3(1)+2y=7
y=2
R=x=1  y=2

3x+2y=24
x+3y=3

3x+2y=24-----------3x+2y=24
-3(x+3y=3)-------  -3x-9y= -9
                        ----------------
                               -7y=15
                                   y= - 15/7
x+3(-15/7)=3
x-45/7=3
7x-45=21
x=66/7
R=x=66/7         y= -15/7

x+y=3500
x-10x/100 + y-8y/100=3170

-90(x+y=3500)---------------> - 90x-90y=-315000
90x+92y=317000----------     90x+92y=317000
                                        -------------------------------
                                               2y=2000
                                                 y= 1000
x+1000=3500
x=2500
R=x=2500   y=1000

2x+3y=-1
3x+4y=0

3x=-4y
x= -4y/3

2(-4y/3)+3y=-1
-8y/3  + 3y=-1
-8y+9y=-3
y=-3

x=-4(-3)/3
x=4
R=x=4    y=-3